DISABILITY, SEXUALITY, AND GENDER IN ASIA intersectionality, human rights, and the law - Zhang, Wanhong, 1976-; Bjørnstøl, Elisabeth Perioli; Ding, Peng (Writer on human rights); Gao, Wei (Writer on human rights); Liu, Hanxu; Liu, Yijun (Writer on human rights) (ROUTLEDGE, 2023)
"This book introduces experiential knowledge of the intersectionality of disability, sexuality, and gender equality issues. Scholars and disabled persons' organizations in different Asian countries such as China, Vietnam, Myanmar, Nepal, and Japan have contributed to the book. It is a preliminary introduction of the frontline practice of Asian disability activism and the experience of women and LGBTIQ people with disabilities. It presents the direct participation of disability advocates in mapping how both women with disabilities and LGBTIQ individuals with disabilities realize their rights such as identity, work rights, personal safety, and sexual rights. Studies presented here explore the experience of empowering diverse disability groups and advocating for equality and non-discrimination. It explains how to use the leverage of the Convention on the Rights of Persons with Disabilities (CRPD) for further human rights campaigns in a broader context for disadvantaged groups. This collection is the product of a participatory research project, which aims to increase local disabled persons' organizations' and NGOs' capabilities in utilizing human rights laws and encourage dialogue and collaboration between academia, people with disabilities, and human rights advocates. It will be essential reading for academics, researchers, policy-makers, and campaign groups"-- Provided by publisher.
Keywords: Women with disabilities -- Legal status, laws, etc. -- Asia.; LAW / General; LAW / Civil Rights; LAW / Comparative; Asia.